Frequency and Diversity of Hybrid Escherichia coli Strains Isolated from Urinary Tract Infections - Nascimento, Júllia A. S. (Microorganisms, 2021)
(1) Background: Hybrid uropathogenic Escherichia coli (UPEC) strains carry virulence markers of the diarrheagenic E. coli (DEC) pathotypes, which may increase their virulence potential. This study analyzed the frequency and virulence potential of hybrid strains among 452 UPEC strains. (2) Methods: Strains were tested for the DEC virulence diagnostic genes’ presence by polymerase chain reaction (PCR). Those carrying at least one gene were classified as hybrid and further tested for 10 UPEC and extraintestinal pathogenic E. coli (ExPEC) virulence genes and phylogenetic classification. Also, their ability to produce hemolysis, adhere to HeLa and renal HEK 293T cells, form a biofilm, and antimicrobial susceptibility were evaluated. (3) Results: Nine (2%) hybrid strains were detected; seven of them carried aggR and two, eae, and were classified as UPEC/EAEC (enteroaggregative E. coli) and UPEC/aEPEC (atypical enteropathogenic E. coli), respectively. They belonged to phylogroups A (five strains), B1 (three), and D (one), and adhered to both cell lineages tested. Only the UPEC/EAEC strains were hemolytic (five strains) and produced biofilm. One UPEC/aEPEC strain was resistant to third-generation cephalosporins and carried bla(CTX-M-15). (4) Conclusions: Our findings contribute to understanding the occurrence and pathogenicity of hybrid UPEC strains, which may cause more severe infections.